2015
DOI: 10.1002/acp.3163
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Modality on Mind Wandering during Comprehension

Abstract: SummaryThe executive resource hypothesis assumes a positive relationship between resource availability and mind wandering. Under the assumption that different modalities of information delivery differentially tax resources, we compared mind wandering across different modalities during the presentation of The Red Headed League (Experiment 1 and 2) and Walden (Experiment 3). An Audio only condition produced the most mind wandering. Two conditions that presumably consumed more executive resources than the Audio O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
12
0
1
Order By: Relevance
“…Resources not used by the task often tend to be allocated to internal thought. As an example, Kopp and D'Mello (2016) compared the proportion of time spent MW (estimated from the proportion of positive responses to thought probes throughout the task) in online learners when learning materials (literary passages) were of higher cognitive demand (i.e., dual-processing channels, visual and auditory) relative to lower cognitive demand (i.e., single-channel, audio only or text only). The results revealed that MW was lowest in the dual-mode condition compared to audio-only, computer-paced reading, and self-paced reading conditions for fast readers.…”
Section: Running Head: Instructor Presence Effectmentioning
confidence: 99%
“…Resources not used by the task often tend to be allocated to internal thought. As an example, Kopp and D'Mello (2016) compared the proportion of time spent MW (estimated from the proportion of positive responses to thought probes throughout the task) in online learners when learning materials (literary passages) were of higher cognitive demand (i.e., dual-processing channels, visual and auditory) relative to lower cognitive demand (i.e., single-channel, audio only or text only). The results revealed that MW was lowest in the dual-mode condition compared to audio-only, computer-paced reading, and self-paced reading conditions for fast readers.…”
Section: Running Head: Instructor Presence Effectmentioning
confidence: 99%
“…Results showed higher rates of MW in the audio only format, with no differences between the audio + text and self-paced reading conditions. These findings were considered in support of the executive resource hypothesis in that rates of MW increase when resources are available to attract attention away from the task towards taskunrelated thoughts and ideas (Kopp & D'Mello, 2016). Although the authors did not directly measure readers' interest, they found that the audio + text condition was the most beneficial to inhibit MW in supposed less interesting texts.…”
Section: Mw and The Impact Of Different Reading Materialsmentioning
confidence: 86%
“…Contrary to their expectations, the results showed that reading aloud produced more MW than silent reading. More recently, Kopp and D'Mello (2016) developed an experimental setting in which adult participants were exposed to three different conditions: reading at their own pace (self-paced reading), listening to an auditory presentation of the materials without any text (audio only), and reading a text with a concurrent presentation of a synchronized narration (audio + text).…”
Section: Mw and The Impact Of Different Reading Materialsmentioning
confidence: 99%
“…With the aid of the detection system, drivers can reacquire the FA state (centralized pattern) whenever the distributed pattern is detected. Future studies can further examine if this pattern also applies to tasks with different spatial, visual, or discourse demands and other modalities (e.g., auditory stimuli) [61].…”
Section: Applications and Future Workmentioning
confidence: 99%